A novel integrated AHP and MULTIMOORA method with interval-valued spherical fuzzy sets and single-valued spherical fuzzy sets to prioritize financial ratios for financial accounting fraud detection - (:unkn) unknown (IOS PRESS, 2022)
Many studies have used different financial ratios for financial accounting fraud detection. This study focuses on multicriteria decision-making (MCDM) for ranking 25 financial ratios with respect to six criteria in detecting financial accounting fraud using interval-valued spherical fuzzy sets (IVSFS) and single-valued spherical fuzzy sets (SVSFS) to overcome uncertainties in decision-making process of financial analysts. This study proposes an integrated Analytic Hierarchy Process (AHP) and Multi-Objective Optimization by a Ratio Analysis plus the Full Multiplicative Form (MULTIMOORA) approach using IVSFS and SVSFS. Comparative results are obtained and discussed in prioritization of financial ratios for both IVSFS and SVSFS.
Keywords: Financial ratios; financial accounting fraud detection; single-valued spherical fuzzy sets (SVSFS); interval-valued spherical fuzzy sets (IVSFS); analytic hierarchy process (AHP); multi-objective optimization by a ratio analysis plus the full multiplicative form (MULTIMOORA); STATEMENT FRAUD; SELECTION; INFORMATION; EXTENSION; MODEL